Making Aromatic Phosphorus Heterocycles More Basic and Nucleophilic: Synthesis, Characterization and Reactivity of the First Phosphinine Selenide. Issue 50 (4th August 2021) - Wossidlo, Friedrich; Frost, Daniel S.; Lin, Jinxiong; Coles, Nathan T.; Klimov, Katrin; Weber, Manuela; Böttcher, Tobias; Müller, Christian
Abstract: The synthesis and isolation of a phosphinine selenide was achieved for the first time by reacting red selenium with 2, 6‐bis(trimethylsilyl)phosphinine. The rather large coupling constant of 1 J P, Se =883 Hz is in line with a P−Se bond of high s ‐character. The σ‐electron donating Me3 Si‐substituents significantly increase the energy of the phosphorus lone pair and hence its basicity, making the heterocycle considerably more basic and nucleophilic than the unsubstituted phosphinine C5 H5 P, as confirmed by the calculated gas phase basicities. NBO calculations further reveal that the lone pairs of the selenium atom are stabilized through donor‐acceptor interactions with antibonding orbitals of the aromatic ring. The novel phosphinine selenide shows a distinct reactivity towards hexafluoro‐2‐butyne, Au(I)Cl as well as i PrOH. Our results pave the way for new perspectives in the chemistry of phosphorus in low coordination. Abstract : The synthesis and isolation of a phosphinine selenide was achieved for the first time. The σ‐electron donating Me3 Si‐substituents significantly increase the energy of the phosphorus lone pair and hence its basicity, making the heterocycle considerably more basic and nucleophilic than the unsubstituted phosphinine C5 H5 P, as confirmed by the calculated gas‐phase basicities. The novel phosphinine selenides show a distinct reactivity towards dienophiles, Au(I)Cl as well as alcohols.